Research on HARQ Technology in Low-Orbit Satellite Communication Network - Runxin ZHANG; Shun ZHANG; Jianpeng MA; Jing ZHANG; Yunfei WU (天地一体化信息网络)
How to extend the HARQ technique to made it suitabled for LEO satellite communication network was explored.First the traditional HARQ technology was expounded.Based on this, the HARQ scheme based on low density parity check code (LDPC) and the HARQ scheme based on message group check code (BCC) were studied respectively, the performance of the schemes was analyzed through simulation.Finally, suitable feedback schemes were analyzed for the retransmission units in the HARQ retransmission mechanism, which provided some reference for the research of HARQ technology in LEO satellite communication networks.